A Multimodality Approach in Designing Learning for Writing Analytical Exposition Texts - Idrus Afandi; Murti Kusuma Wirasti; Cecep Kustandi (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
This study aims to investigate the use of a multimodal approach in designing learning to write analytical exposition text. The learning design is based on the five steps of Universal Design for Learning (UDL) and iterative backward design to optimize inclusive and relevant learning. UDL steps include setting clear objectives, anticipating learner needs, developing measurable objectives and assessment plans, establishing learning experiences, and reflecting and new understanding for educators. A multimodal approach is used to engage students in learning and facilitate the development of student's critical analysis skills and creativity. The results of this learning design show that the implementation of a multimodal approach using UDL steps and iterative backward design can improve the effectiveness of learning to write analytical exposition text. Learning design that focuses on clear objectives, accommodating students' needs, and measurable assessment, This research provides valuable insights for educators in designing learning to write analytical exposition texts utilizing a multimodal approach and UDL steps. This research provides valuable insights for educators in designing learning to write analytical exposition texts that utilize multimodal approaches and UDL steps. The implications of this research can be used as a reference in designing inclusive, relevant, and diverse learning to improve students' understanding of analytical exposition text writing.